Pengebangan Design Pembelajaran Tematik untuk Meningkatkan Pemahaman Konsep Bilangan Desimal Siswa Sekolah Dasar - Erna Wirda; Rahmah Johar; M. Ikhsan (Universitas Syiah Kuala, 2015)
Abstract: The decimal number is a subject matter that is difficult to understand by elementary school student. Fractions and decimals is seen by the student as two different things. Students are difficult to understand that 1/4 is equal to 0.25 for the different way of writing. This condition causes the teachers need to design learning trajectory that can facilitate students to understand the decimals material. The purpose of this study was to develop a Hypothetical Learning Trajectory (HLT) that can help students understand the concept of decimal numbers. This study involves a teacher and 36 students of fourth grade of elementary school in Banda Aceh. The method used was a design research method that was done by using two cycles they are pilot experiments and teaching experiments. Each of them consists of three stages: (i) preparing for the experiment, (ii) the teaching experiment, and (iii) the retrospective analysis. Research data collection using two kinds of instruments that were the main instrument who was the researcher's herself and supporting instruments consisting of student activity sheets, observation sheets, interview, and field notes. The results showed HLT that was developed can help students understand the concept of a decimal number.Keywords: Hypothetical learning trajectory, conceptual understanding, decimal numbers